Dark Tourism, Emotions, and Postexperience Visitor Effects in a Sensitive Geopolitical Context: A Chinese Case Study. (July 2018) - Weaver, David; Tang, Chuanzhong; Shi, Fangfang; Huang, Ming-Feng; Burns, Kevin; Sheng, Ang
Engaging the neglected intersection between dark tourism, the visitor postexperience and geopolitics, this research reports the findings from a survey of 1, 082 domestic visitors to Lushun Prison Museum in Dalian, China, a Japanese-era incarceration and punishment site that projects hegemonic anti-Japanese social representations. Most respondents reported strong emotional reactions and elevated patriotism along with worsened attitudes toward Japan, Japanese products and, to a lesser degree, Japanese people, suggesting negative implications for the increasingly tense China–Japan bilateral relationship. However, sample diversity is indicated by the revelation of small Japan-neutral clusters whose members are more likely to express contemplation and pity as dominant emotions rather than the anger and hate of the majority, and who qualify the dominant social representations accordingly. Communist Party membership, age, lack of student affiliation, and not having Japanese friends or knowing any Japanese people were all associated with Japan-negative perceptions and intentions.